Fabrication of alginate modified brushite cement impregnated with antibiotic: Mechanical, thermal, and biological characterizations. Issue 9 (29th May 2019) - Dabiri, S. M. Hossein; Lagazzo, Alberto; Aliakbarian, Bahar; Mehrjoo, Morteza; Finocchio, Elisabetta; Pastorino, Laura
Abstract: Treatment of postsurgical infections, associated with orthopedic surgeries, has been a major concern for orthopedics. Several strategies including systematic and local administration of antibiotics have been proposed to this regard. The present work focused on fabricating alginate (Alg) modified brushite (Bru) cements, which could address osteogeneration and local antibiotic demands. To find the proper method of drug incorporation, Gentamicin sulfate (Gen) was loaded into the samples in the form of solution or powder. Several characterization tests including compression test, morphology, cytotoxicity, and cell adhesion assays were carried out to determine the proper concentration of Alg as a modifier of the Bru cement. The results indicated that addition of 1 wt% Alg led to superior mechanical and biological properties of the cement. Moreover, Alg addition changed the morphology of the cement from plate and needle‐like structures to petal‐like structure. Fourier transform infrared spectroscopy results confirmed the successful loading of Gen on the cements, specifically when Gen solution was used, and X‐Ray Diffractometer result indicated that Gen caused a decrease in crystalline size. Furthermore, thermal analysis revealed that Gen‐loaded sample had more stable structure as the transformation temperature slightly shifted to a higher one. The stability study confirmed the chemical stability and adequate mechanical performance of the cements within 1 month of soaking time. Finally, the addition of Alg has a positive impact on the release behavior at low concentration of Gen solution so that 20% decrease within 2 weeks of release experiment was remarkably detected.